Legal Certainty and the Harmonization of the Principle of Prudence: A Reconstruction of Bank Compliance Parameters in the Discourse on the Business Judgment Rule - Rizki Pratama; Ida Nadirah (PT FORMOSA CENDEKIA GLOBAL, 2026)
The banking sector plays a crucial role in national economic development and must operate in accordance with prudential banking principles. However, legal uncertainty arises due to the clash of norms between the regulations governing the Board of Directors' duties under Law No. 40 of 2007 concerning Limited Liability Companies (UU PT) and criminal liability under Law No. 10 of 1998 concerning Banking. This research aims to analyze the harmonization of these regulations and propose a reconstruction of prudential parameters to avoid the criminalization of business risks. The research adopts a normative legal method, and findings indicate that the lack of clear